Soil Water Conservation. Dynamics and Impact - Pirastru, Mario (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Human needs like food and clean water are directly related to good maintenance of healthy and productive soils. A good understanding of human impact on the natural environment is therefore necessary to preserve and manage soil and water resources. This knowledge is particularly important in semi-arid and arid regions, where the increasing demands on limited water supplies require urgent efforts to improve water quality and water use efficiency. It is important to keep in mind that both soil and water are limited resources. Thus, wise use of these natural resources is a fundamental prerequisite for the sustainability of human societies. This book collects 15 original scientific contributions addressing the state of the art of soil and water conservation research. Contributions cover a wide range of topics, including (1) recovery of soil hydraulic properties; (2) erosion risk; (3) novel modeling, monitoring and experimental approaches for soil hydraulic characterization; (4) improvement of crop yields; (5) water availability; and (6) soil salinity. This collection provides more insights into conservation strategies for effective and sustainable soil and water management.